2000
DOI: 10.1128/iai.68.2.839-847.2000
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Role of Cytotoxic Necrotizing Factor 1 Toxin fromEscherichia coliin Bacterial Pathogenicity and Host Cytokine Response in Infected Germfree Piglets

Abstract: Some Escherichia coli strains isolated from intestinal or extraintestinal infections in pigs produce cytotoxic necrotizing factor 1 (CNF1). In order to analyze the role of CNF1 in the pathogenesis of porcine colibacillosis, newborn colostrum-deprived germfree piglets were orally inoculated with a wild-type CNF1-producing strain (M623) or with an isogenic cnf1 mutant (M623⌬CNF1). The two isogenic strains induced a high mortality with similar lung and serosal inflammatory lesions, indicating that both strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 66 publications
2
33
1
Order By: Relevance
“…2, Tables 2 and 3). Fournout et al also reported that intestinal colonization by nonpathogenic E. coli did not cause an inflammatory reaction in piglets (12). Although Bétis et al (4) showed that nonmotile E. coli laboratory strain HB101 acquired an ability to induce IL-8 after transformation with plasmid carrying a kind of Afa gene (daa), it was not shown whether the level of IL-8 was similar to those caused by the well-established enteropathogenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…2, Tables 2 and 3). Fournout et al also reported that intestinal colonization by nonpathogenic E. coli did not cause an inflammatory reaction in piglets (12). Although Bétis et al (4) showed that nonmotile E. coli laboratory strain HB101 acquired an ability to induce IL-8 after transformation with plasmid carrying a kind of Afa gene (daa), it was not shown whether the level of IL-8 was similar to those caused by the well-established enteropathogenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Van Bost et al (2001b) reported that CNF2-producing strains were able to colonize the intestines, cause long-lasting diarrhea, and invade the blood stream of newborn colostrum-restricted calves after experimental inoculation through the oral route. A previous report on the experimental infection of germfree colostrum-deprived newborn piglets showed no evidence for a pathogenic role of CNF1 in the development of diarrhea (Fournout et al 2000). To date, there is no report on a comprehensively case-control epidemiological study of the association of CNF-producing E. coli strains with human diarrheal diseases.…”
mentioning
confidence: 93%
“…On the other hand, most of the NTEC1 isolates harbour sequences typical of the P®mbrial adhesin family and either one S-®mbrial (Sfa or F1C) (Fournout et al, 2000) or the AfaVIII-a®mbrial adhesins (Mainil et al, 1997(Mainil et al, , 1999Lalioui et al, 1999;Ge Ârardin et al, 2000), which are all located on the chromosome. The pap/prs gene clusters coding for P®mbriae and the cnf1 gene are actually associated with a hly operon coding for the ahemolysin, forming the so-called pathogenicity island 5 or Pai 5 (Blum et al, 1995;De Rycke et al, 1999;Dozois and Curtiss III, 1999).…”
Section: Introductionmentioning
confidence: 99%